Pengaruh Pemanfaatan Bantuan Dana Pendidikan dan Motivasi Belajar Terhadap Hasil Belajar Mahasiswa S1 Pendidikan Ekonomi Angkatan 2012 Universitas Negeri Malang - Farikhatul Nadiroh; Wahjoedi * (Jurnal Pendidikan Ekonomi (Economic Education Journal), 2016)
This research is aiming to know the effect of Scholarship Use and Learning Motivation toward Learning Result of Undergraduate Economic Education College Students class of 2012, State University of Malang. This research used quantitative descriptive research. There were 64 persons as the population. The data collection used questionnaires and documentations. Meanwhile, the data were analyzed using SPSS 23.00 for Windows. The results of this research indicated that Scholarship Use and Learning Motivation were a significant and positif effect toward learning results of undergraduate economic education college students class of 2012 who received scholarship on 2015.Keywords: Scholarship Use, Learning Motivation, and Learning Result.